A systematic review to identify EFL teachers’ training needs for professional development programs - Abdullah Alzahrani, Mona (HRMARS, 2021)
As being an international language, English is described as a communication tool all over the world. The field of teaching this language is affected by the changeable characteristics of this technological era. Therefore, learners and teachers are changing and in order to meet the demands of this change, teachers must keep up to date and improve their teaching practices and beliefs. This can be done through professional development programs (PDPs) and in-service training for English as foreign Language (EFL) teachers. The purpose of this systematic review was to identify EFL Teachers’ needs for PDPs. A total of 11 empirical studies were chosen for thorough review upon detailed selection criteria. The reviewed papers were related to in-service EFL teachers’ training needs in journal articles published between 2015 and 2019. In this review, methods and results of different research studies were analyzed via a collection of systematic techniques. The results of the study indicated that there were eight categories of EFL teachers’ needs for PDPs. Through this systematic review, authors provided recommendations for researchers and PDPs designers.